Has Multiculturalism Really Failed?: A Canadian Muslim Perspective - Nagra, Baljit (Religions, 2013)
In recent years, claims that multiculturalism has created segregated communities, encouraged terrorism, and failed to foster shared national identities in western nations have gained popularity. In this paper, we use young Canadian Muslims’ lived experience of multiculturalism to reflect on this debate. Contrary to popular rhetoric, our interviews of 50 young Muslim adults show that many maintain a dual Canadian-Muslim identity by utilizing the ideology of multiculturalism, even though they are increasingly stigmatized for their religion. These findings lead us to problematize the discourse surrounding the ‘failure’ of multiculturalism and to highlight the contradictions within it.